Investigation of charge collection pathways in mesoscopic solar cells - Chua, Julianto (2014)
Mesoscopic solar cells, including Dye-sensitized Solar Cells (DSC), are a promising technology that offers efficiency exceeding 10% at reasonable costs and ease of assembly. One of the key parameters that determine the efficiency of these solar cells is the electron dynamics within the mesoporous titania layer. This project aims to study the parameters that determine charge collection within the mesoscopic solar cells and proposes novel charge collection strategies. The approach described in the project utilizes lithographically patterned metal grid electrodes (MGE) as a replacement for transparent conducting oxide (TCO) which has been conventionally used as the charge collector. The MGE offers an immediate benefit of eliminating the conventional DSC reliance on TCO. Furthermore, the proposed MGE based DSC also offers an inherent prospect for demonstrating horizontal electron collection pathway in DSC. Modulation of electron collection behaviour can be achieved by varying the spacing between the grids. The first study involves applying the MGE approach to the classic liquid state DSC. It is observed that for the best device performance, a balance between effective active area (due to the opaque MGE blocking photons) and electron collection efficiency (due to the different average electron transport distances for various grid spacing) has to be reached. In the case of liquid state DSC, 40um grid spacing was found out to be the optimal design with highest device power conversion efficiency (PCE) of 6.2% compared to the conventional FTO based DSC (7.1% efficient). Electron collection behaviour of these MGE devices were characterized via Electrochemical Impedance Spectroscopy (EIS), which showed that electron transport resistance decreases with reduced grid spacing. A set of design rules had been designed to ensure optimal electron collection. Firstly, the grid spacing has to be greater than two-third of the electron diffusion length (EDL). Secondly, the grid thickness should be at least thicker than photoelectrode thickness minus a third of EDL. Thirdly, a grid width of no more than a tenth of grid spacing should ensure sufficiently large effective active area. The understanding of charge collection behaviour in liquid state DSC can be extended to more novel solid state counterpart (where the liquid electrolyte is replaced by a polymeric hole transporting layer) since the underlying working principle is similar. In the case of such solid state DSC (ssDSC), 20um spacing device was found out to be the optimal design that best compromises the effective active area and electron collection efficiency; PCE of 2.1% compared to the conventional based FTO device which is 3% efficient. The best efficiency being obtained for narrower grid spacing than the liquid counterpart, indicates the lower EDL for the solid-state cells. Additionally, a simple two-electrode device configuration was studied to complement the EIS measurements of ssDSC, which unambiguously suggested that hole transport is faster than electron transport in ssDSC. Finally, the MGE approach was implemented in the recently developed methyl-ammonium-lead-iodide perovskite solar cells. It was found out that as the grid spacing increased beyond 10 μm (6% PCE, compared to conventional FTO based standard reference cell 8.5%), the efficiency dropped gradually. Electron diffusion length in this novel type of mesoscopic solar cell was estimated by benchmarking the procedure on the well-studied liquid and solid state DSC and yielded a value between 3-5 μm.